Comparison of the accommodation theories of Coleman and of Helmholtz by finite element simulations - Martin, Heiner; Guthoff, Rudolf; Terwee, Thom; Schmitz, Klaus-Peter (Vision research (Oxford), 2005)
The accommodation process of the human eye is still a controversial subject. Coleman assumes that the lens, together with the zonula fibers, forms a diaphragm which is held in a catenary shape due to the pressure difference between the aqueous and vitreous body of the lens. The aim of the paper is to compare the results of two simulations (according to the Helmholtz and to the Coleman theories) with ultrasonographic data. An axisymmetric static finite element model of the lens was generated using the literature data for geometry, material properties and loads. The refractive power of the lens was calculated for two different ages (29 and 45 years). The application of a pressure to the posterior lens surface did not yield an increase in refractive power change during accommodation. Rather a decrease in accommodation related refractive power was found. Physiologically relevant refractive power changes are obtained by a simulation in accordance with the Helmholtz theory. A simulation in accordance with the Coleman theory does not yield physiological values of refractive power change.